Knowledge and confidence in managing obstructive sleep apnea patients in Canadian otolaryngology - head and neck surgery residents: a cross sectional survey - Saad Ansari; Amanda Hu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Obstructive sleep apnea is an expected competency for Otolaryngology - Head and Neck surgery residents and tested on the Royal College of Physicians and Surgeons examination. Our objective was to evaluate the knowledge, attitudes and confidence of Canadian Otolaryngology - Head and Neck surgery residents in managing Obstructive Sleep Apnea (OSA) patients. Methods An anonymous, online, cross-sectional survey was distributed to all current Canadian Otolaryngology-Head and Neck surgery residents according to the Dillman Tailored Design Method in English and French. The previously validated OSA Knowledge and Attitudes (OSAKA) questionnaire was administered, along with questions exploring resident confidence levels with performing OSA surgeries. Descriptive statistics, Wilcoxon Rank Sum and unpaired Student’s t tests were calculated in Excel. Results Sixty-six (38.4%) out of 172 residents responded (60.6% male; 80.3% English-speaking). Median OSAKA knowledge score was 16/18 (88.9%; Interquartile range: 14–16). Although all respondents believed that OSA was an important clinical disorder, only 45.5% of residents felt confident in managing OSA patients, while only 15.2% were confident in managing continuous positive airway pressure therapy (CPAP). Senior residents were more confident than junior residents in identifying OSA patients (96.7% vs 69.4%; p < 0.005) and managing the disease (60.0% vs. 33.3%; p = 0.03), including CPAP (26.7% vs. 5.6%; p = 0.01). Residents had lowest confidence levels in performing tongue base suspension (1.5%), transpalatal advancement pharyngoplasty (3.0%), and laser assisted uvulopalatoplasty (6.1%). Highest confidence levels were described in performing septoplasty (56.1%), adult tonsillectomy (75.8%), and tracheotomy (77.3%). Conclusions Otolaryngology - Head and Neck surgery residents’ knowledge of OSA was very good; however, confidence levels for managing OSA and performing OSA surgeries were varied. Several areas of perceived strengths and weaknesses in OSA training were identified by Canadian Otolaryngology - Head and Neck surgery residents.